Solar radiation stimulates release of semi-labile dissolved organic matter from microplastics - Wang, Jun; Cai, Ruanhong (Frontiers in Marine Science, 2023)
Microplastics can release dissolved organic matter (DOM) into seawater under solar radiation exposure. However, the molecular composition and bioavailability of this DOM remain to be investigated. Here, two popular microplastics, low-density polyethylene (LDPE) and polystyrene (PS), were exposed to solar radiation in an artificial seawater for 10 days. The solar-induced LDPE-DOM and PS-DOM were molecularly characterized using ultra-high-resolution mass spectrometry, and were further incubated in a coastal microbial assemblage to examine their bioavailability. Results showed that solar radiation stimulated release of DOM from the microplastics. Dissolved organic carbon concentration analysis indicated that approximately 19.03 µg C L–1 and 3.85 µg C L–1 were released from each gram of LDPE and PS per day, respectively. Molecular composition analysis showed that both the LDPE-DOM and PS-DOM comprised a proportion of nitrogen- and sulfur-bearing molecules, and that the LDPE-DOM molecules were associated with lower molecular abundance and values of double-equivalent-bond and aromatic-index, but higher average hydrogen-to-carbon ratio than that in the PS-DOM. In addition, a proportion of the assigned formulas in LDPE-DOM (22.3%) and PS-DOM (55.8%) could be found in a coastal-DOM sample, suggesting their potential contribution to coastal DOM pool. The further incubation experiment showed that nearly 18.7% of LDPE-DOM and 9.5% of PS-DOM were utilized or transformed within 30 days. Still, a fraction of the solar-induced LDPE-DOM and PS-DOM resisted rapid microbial utilization, remained as semi-labile DOM. These results underlined unaccounted consequences of microplastic-derived DOM in coastal DOM pool.